BasicS, an Euphresco International Network on Renewable Natural Substances for Durable Crop Protection Products - Marchand, Patrice A.; Davillerd, Yann; Riccioni, Luca; Sanzani, Simona Marianna; Horn, Nico (Chronicle of Bioresource Management, 2023)
Under the European Union aegis, a new round of non-competitive projects is being initiated via Euphresco. The topic description developed within the consortium created within Euphresco research coordination is the development of the basic substance for management of pests/vectors via natural compounds. Basic substances are approved for use in the European Union and are products which are already sold for certain purposes, e.g., as a foodstuff or a cosmetic, but which can also serve as plant protection products. A list of 23 basic substances approved is available through the EU Pesticides database. These substances are mostly biorationals (medicinal plant extracts like Equisetum, Urtica, Salix and Mustard seeds powder), products used in human medicine (chitosan, calcium hydroxide), food compounds (milk, whey, vinegar, beer, fructose, sucrose, lecithin, vegetable oils, bicarbonate, sodium chloride and onion) or common substances (talc, amino acids, diammonium phosphate, clay and charcoal) but used as means of plant protection. The project aims to test and validate the use of basic substances as plant protection measures. All partners have experience in the application of basic substances and potential basic substances in the field or postharvest, in their mechanisms of action, in their chemical characterization or in their approval process.